Переведення Київського державного інституту кінематографії до Москви: нові документи РДАЛМ - Безручко, О. (Архіви України, 2009)
The author analyzes texts of unknown study programs’ art faculty of Kyiv State Institute of cinema Art, which where transferring at 1938 year to the Allunion State Institute of cinema Art.